Deep‐Red Lasing and Amplified Spontaneous Emission from Nature Inspired Bay‐Annulated Indigo Derivatives. Issue 2 (14th November 2019) - Shukla, Atul; Wallwork, Nicholle R.; Li, Xin; Sobus, Jan; Mai, Van T. N.; McGregor, Sarah K. M.; Chen, Kay; Lepage, Romain J.; Krenske, Elizabeth H.; Moore, Evan G.; Namdas, Ebinazar B.; Lo, Shih‐Chun
Abstract: While noteworthy progress has been made on organic solid‐state lasers with low amplified spontaneous emission (ASE) thresholds and high optical gains in blue and green colors, the same advancement has not been achieved for red laser dyes. This is mainly due to their low photoluminescence quantum yields (PLQYs) because of "energy bandgap law." Here, a new family of solution‐processable organic semiconductor laser dyes based on a bay‐annulated indigo derivative (Cibalackrot) with deep‐red emission is reported. They exhibit excellent PLQYs and low ASE thresholds (9.6 µJ cm −2 ) with deep‐red emission when blended in a mixed host of 1, 3‐bis( N ‐carbazolyl)benzene (mCP) and 2‐hydroxyphenylbenzothiazole (HBT). In contrast to a single blend in mCP, the co‐blend films are found to significantly enhance the photostability by retaining 90% of initial ASE intensity even after continuous pumping with over 9000 pulses at a pump input energy twice that of the ASE threshold, which can be attributed to efficient cascade energy transfer from mCP to HBT and then to the Cibalackrot chromophore. Low lasing threshold of 6 µJ cm −2 is further achieved at 641 nm by using distributed feedback gratings. Transient absorption spectroscopy measurements indicate that the dye has extremely low yield of triplet excited‐state under optical excitation. The results show Cibalackrot derivatives to be a promising new family of organic deep‐red laser dyes. Abstract : Solution processable organic semiconductor laser dyes with deep‐red emission are synthesized and characterized to show excellent photoluminescence quantum yields and low amplified spontaneous emission thresholds with high photostability.